2021
DOI: 10.1016/j.cub.2021.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Proximity labeling reveals non-centrosomal microtubule-organizing center components required for microtubule growth and localization

Abstract: Highlights d Proximity labeling in living C. elegans identifies ncMTOC proteins d WDR-62, VAB-10B, and actin filaments drive ncMTOC function and assembly d Functionally distinct ncMTOC modules control microtubule growth and localization d The apical ncMTOC is physically and functionally distinct from the centrosome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 89 publications
(126 reference statements)
5
44
0
Order By: Relevance
“…This property may help to explain how acentrosomal MTOCs form in cells where both PCM proteins and PCM-independent microtubule stabilizers such as CAMSAPs are present. Two well studied examples of such systems are the MTOCs at the Golgi membranes and the apical cortex of epithelial cells, where CAMSAPs and PCM proteins are present simultaneously and may cooperate with each other or play redundant roles (Goldspink et al, 2017; Nashchekin et al, 2016; Noordstra et al, 2016; Sanchez et al, 2021; Toya et al, 2016; Wang et al, 2015; Wu et al, 2016; Zhu and Kaverina, 2013). We found that CAMSAP2­stabilized minus ends can exert a highly dominant effect on PCM organization, and this property likely explains how the Golgi, which anchors CAMSAP2-stabilized microtubules, recruits PCM and becomes the major MTOC in cells lacking centrosomes.…”
Section: Discussionmentioning
confidence: 99%
“…This property may help to explain how acentrosomal MTOCs form in cells where both PCM proteins and PCM-independent microtubule stabilizers such as CAMSAPs are present. Two well studied examples of such systems are the MTOCs at the Golgi membranes and the apical cortex of epithelial cells, where CAMSAPs and PCM proteins are present simultaneously and may cooperate with each other or play redundant roles (Goldspink et al, 2017; Nashchekin et al, 2016; Noordstra et al, 2016; Sanchez et al, 2021; Toya et al, 2016; Wang et al, 2015; Wu et al, 2016; Zhu and Kaverina, 2013). We found that CAMSAP2­stabilized minus ends can exert a highly dominant effect on PCM organization, and this property likely explains how the Golgi, which anchors CAMSAP2-stabilized microtubules, recruits PCM and becomes the major MTOC in cells lacking centrosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In polarized epithelial cells in flies, worms and mammals, CAMSAP homologs were shown to contribute to the organization of apico-basal microtubule arrays that have their minus-ends anchored at non-centrosomal, apical MTOCs ( Meng et al, 2008 ; Tanaka et al, 2012 ; Wang et al, 2015 ; Nashchekin et al, 2016 ; Ning et al, 2016 ; Noordstra et al, 2016 ; Toya et al, 2016 ). The contribution of CAMSAPs to apical minus-end anchoring may involve their ability to decorate microtubule minus-ends and to interact with spectraplakins that tether microtubules to the cortical actin network ( Khanal et al, 2016 ; Nashchekin et al, 2016 ; Sanchez et al, 2021 ). In the larval epidermis in C. elegans , the CAMSAP homolog PTRN-1 functions redundantly with NOCA-1, a worm ninein homolog.…”
Section: Microtubule Anchoring Factors and Mechanismsmentioning
confidence: 99%
“…This protocol describes the steps for conducting biotin-ligase based proximity labeling in living C. elegans using TurboID in intestinal cells ( Sanchez et al, 2021 ). We have also previously shown examples of proximity labeling using miniTurbo ( Branon et al, 2018 ).…”
Section: Before You Beginmentioning
confidence: 99%
“…This protocol is useful for targeted in vivo protein network profiling. For complete details on the use and execution of this protocol, please refer to Sanchez et al (2021) .…”
mentioning
confidence: 99%
See 1 more Smart Citation